PENGARUH KOMUNIKASI, KEPEMIMPINAN, DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI - Adinda Chandralela; Ahmad Yani Hazir (LPPM STIE PERTIBA Pangkalpinang, 2017)
This study aim is to analyze the influence of communication, leadership, and organizational culture on the performance of Civil Service Office of Revenue, Financial Management and Regional Assets Province of Bangka Belitung Islands. The population used as the sample used is 117 Civil Servants of the Department of Revenue, Financial Management and Regional Assets Province of Bangka Belitung Islands. The research instrument used questionnaires, arranged on a scale of 1-5. Data analysis techniques used are validity test, reliability test, normality test, and hypothesis testing. The results showed that communication and leadership contributed simultaneously and significantly to organizational culture and leadership and organizational culture also contributed and simultaneously to the performance of employees.